Prototype Kacamata Sensorik Untuk Tunanetra Berbasis Mikrokontroler - Dedy Hendryadi; Juniarti Iryani; M Azran (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2022)
Technological developments have changed people's lives who have physical limitations, including blind people. Braille's discovery makes them possible to read and operate a computer. However, they still need a stick and the closest person to guide them to carry out daily activities. Thus, to overcome this problem, this research produces object detection glasses for the visually impaired based on a microcontroller. These glasses are used to detect objects in front of the visually impaired when walking. These glasses are prototypes that can be worn by blind people and work by detecting objects in front and below using three ultrasonic sensors based on a predetermined distance of a minimum of 50 cm and a maximum of 100 cm, where the ultrasonic sensor is the reference point. This tool works by giving a warning to the patient via the microcontroller to the buzzer. This study concludes that these sensory glasses can provide a warning in the form of sound to the user when they find an object in front of them at a predetermined distance.